Repeat ipsilateral ectopic gestation: a series of 3 cases (2006)
Ectopic pregnancy remains an important cause of maternal mortality and morbidity as well as early foetal wastage in Nigeria and in other developing countries. We report 3 different cases of repeat ipsilateral ectopic pregnancy seen in the gynaecological emergency unit of the University College Hospital, Ibadan. Cases of repeat ectopic pregnancy often gives rise to diagnostic dilemma, and this becomes more difficult when it occurs at an ipsilateral location.